Piano concertos Nos. 4 and 5 ("Emperor"): with orchestral reduction for second piano - Beethoven, Ludwig van. 1770-1827 (Dover orchestral scores, 1995)
This volume contains two of Beethoven´s most loved and widely performed piano concertos, printed in the tradicional format for twp pianos: Piano I is the solo part, Piano II, a piano reduction of the orchestral score.